1992
DOI: 10.1148/radiology.185.2.1410381
|View full text |Cite
|
Sign up to set email alerts
|

Expandable intravascular catheter: percutaneous use for endoluminal retrievals.

Abstract: Percutaneous use of an expandable vascular access catheter that can be deployed to temporarily occlude the entry vessel during retrieval of embolic material is described. The catheter was used to facilitate removal of two intraarterial objects, a postangioplasty free atheroma fragment and a displaced Gianturco coil. The expanded catheter end was equal to the arterial lumen, thus preventing distal embolization. The large distal lumen also facilitated plaque or foreign body removal by allowing deployment of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…4 Balloon angioplasty has also been used to assist in intravascular foreign body removal and manipulate intravascular stents. 5 …”
Section: Discussionmentioning
confidence: 99%
“…4 Balloon angioplasty has also been used to assist in intravascular foreign body removal and manipulate intravascular stents. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Mismatch between the size of the introducer device and the vessel lumen, however, was a primary limitation. Recently, a variable-diameter sheath has been devised to overcome this problem [5,6]; however, this was made only for intraoperative insertion and no systematic evaluation has been performed. Vorwerk et al [7,8] suggested a tulip sheath that could be inserted percutaneously and consisted of a costly self-expandable stent (Wallstent, Schneider Europe, Zurich, Switzerland).…”
Section: Discussionmentioning
confidence: 99%